2020
DOI: 10.2147/ndt.s195840
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transcranial Direct Current Stimulation in Patients with Anxiety: Current Perspectives</p>

Abstract: Anxiety is one of the most prevalent and debilitating psychiatric conditions worldwide. Pharmaco-and psycho-therapies have been employed in the treatment of human anxiety to date. Yet, either alone or in combination, unsatisfactory patient outcomes are prevalent, resulting in a considerable number of people whose symptoms fail to respond to conventional therapies with symptoms remaining after intervention. The demand for new therapies has given birth to several noninvasive brain stimulation techniques. Transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 44 publications
1
54
0
1
Order By: Relevance
“…Few studies have reported the effect of tDCS on the anxiety disorders and fewer in patients with substance dependence disorders (Hampstead et al, 2016;Kar and Sarkar, 2016). Some researchers have proposed the placement of cathode electrode on the right prefrontal cortex and anode electrode on the left prefrontal cortex (Stein et al, 2020). The hypothesis is that the cathodal stimulation may reduce cortical excitability in anxiety disorders, which accompany cortical excitability.…”
Section: Effects On Depression and Anxietymentioning
confidence: 99%
“…Few studies have reported the effect of tDCS on the anxiety disorders and fewer in patients with substance dependence disorders (Hampstead et al, 2016;Kar and Sarkar, 2016). Some researchers have proposed the placement of cathode electrode on the right prefrontal cortex and anode electrode on the left prefrontal cortex (Stein et al, 2020). The hypothesis is that the cathodal stimulation may reduce cortical excitability in anxiety disorders, which accompany cortical excitability.…”
Section: Effects On Depression and Anxietymentioning
confidence: 99%
“…Bifrontal 2 mA stimulation with cathode over the right and anode over the left DLPFC was performed on a recently published controlled randomized trial, supporting the efficacy of tDCS in the treatment of PTSD ( 211 ). In contrast, evidence for tDCS in the treatment of generalized anxiety disorder is less robust ( 212 ). A randomized controlled trial showed improvement in physical stress symptoms but not in the primary outcome measure (Hamilton Anxiety Rating Scale) in the active group in comparison to sham ( 213 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because of its non-invasive nature, highly controlled sham condition, and relatively low cost compared to other neuromodulation techniques, tDCS quickly arises as a promising therapeutic tool. Indeed, many several systematic reviews and meta-analyses of randomized controlled trials indicated the safety and therapeutic efficacy of tDCS for a wide range of mental disorders (for a review, see Tortella et al, 2015), including, among others, depression and mood disorders (Borrione et al, 2018;Dondé et al, 2018;Razza et al, 2020), anxiety disorders (e.g., Stein et al, 2020;Yosephi et al, 2019), psychotic disorders (e.g., Lee et al, 2018), pain-related disorders (e.g., Zortea et al, 2019), and eating disorders (e.g., Dalton et al, 2018). Hence, this literature has prompted an exceptionally positive prospect vis-à-vis tDCS as a therapeutic tool.…”
Section: A Systematic Review Of the Sham-controlled Studies In Healthmentioning
confidence: 99%